2015
DOI: 10.1002/ima.22141
|View full text |Cite
|
Sign up to set email alerts
|

Graph-theory-based spectral feature selection for computer aided diagnosis of Parkinson's disease using T1-weighted MRI

Abstract: Introduction: Parkinson's disease (PD) is a neurological disorder, which is diagnosed on the basis of clinical history and examination alone as there are no diagnostic tests available. However, the current diagnosis highly depends on the knowledge and experience of clinicians and hence subjective in nature. Thus, the focus of this study is to develop a computer-aided diagnosis (CAD) method using T1-weighted magnetic resonance imaging (MRI) to differentiate PD from controls. Method: The proposed method utilizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Recent studies on manifold learning theory [ 29 , 30 ], spectral graph theory [ 31 , 32 ] and their applications [ 33 – 38 ] show that the geometric and topological structure of data points may be maintained when they are mapped from high dimensional space into low dimensional space. Considering that the similarity matrix w d and w s not only can be defined to represent statistical correlation but also can be regarded as geometric properties of the data points, we introduce the similarity constraint terms R X and R Y : where denotes the similarity between the drug d i and the drug d j , which is calculated in the drug feature space; denotes the similarity between the disease dis i and the disease dis j , which is calculated in the disease feature space.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies on manifold learning theory [ 29 , 30 ], spectral graph theory [ 31 , 32 ] and their applications [ 33 – 38 ] show that the geometric and topological structure of data points may be maintained when they are mapped from high dimensional space into low dimensional space. Considering that the similarity matrix w d and w s not only can be defined to represent statistical correlation but also can be regarded as geometric properties of the data points, we introduce the similarity constraint terms R X and R Y : where denotes the similarity between the drug d i and the drug d j , which is calculated in the drug feature space; denotes the similarity between the disease dis i and the disease dis j , which is calculated in the disease feature space.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of previous study [53,54], the geometric properties of data points may be kept when they are mapped from high-rank space into low-rank space. Disease similarity S d and miRNA similarity S m can indicate geometric structure of data points, so we present similarity constraint termsS U and S V as follows:…”
Section: Similarity Constrained Matrix Factorizationmentioning
confidence: 99%
“…Since Equation (6) maps drugs and diseases into a lowdimensional space, a natural idea occurs that the lowdimensional representations should preserve the underlying interconnection information of drugs and diseases. Studies on manifold learning (Belkin et al, 2006;Ma and Fu, 2012;Zhang et al, 2018a), spectral graph theory (Chung, 1997;Rana et al, 2015) and their applications (Zhang et al, 2016a(Zhang et al, , 2017a(Zhang et al, ,b,c, 2018bRuan et al, 2017) have shown that the learning performance can be signally enhanced, if the local topological invariant properties are preserved. Cai et al (2011) proposed Laplacian regularizations to achieve this goal.…”
Section: Objective Function Of Cmfmtlmentioning
confidence: 99%